Вы находитесь на странице: 1из 7

International

OPEN

Journal

ACCESS

Of Modern Engineering Research (IJMER)

On ranges and null spaces of a special type of operator named


. Part I
Rajiv Kumar Mishra
Assistant Professor, Department of Mathematics , Rajendra College, Chapra (Jai Prakash University,Chapra)
Bihar-841301

ABSTRACT: In this article, has been introduced which is a generalization of trijection


operator as introduced in P.Chandras Ph. D. thesis titled Investigation into the theory of operators
and linear spaces (Patna University,1977). We obtain relation between ranges and null spaces of two
given under suitable conditions.
Key Words: projection, trijection,

I. Introduction
Dr. P. Chandra has defined a trijection operator in his Ph.D. thesis titled Investigation into the
theory of operators and linear spaces. [1]. A projection operator E on a linear space X is defined as 2 =
as given in Dunford and Schwartz [2] , p .37 and Rudin [3], p.126. In analogue to this , E is a trijection operator
if 3 = . It is a generalization of projection operator in the sense that every projection is a trijection but a
trijection is not necessarily a projection.

II. Definition
Let X be a linear space and E be a linear operator on X. We call E a if
3 + 2 = 1 + , being a scalar. Thus if = 0
, 3 = . . trijection. We see that 2 = 3 = and above condition is satisfied. Thus a
projection is also a .

III.

Main Results

3.1 We first investigate the case when an expression of the form 2 + is a projection where E is a
. For this we need
( 2 + )2 = 2 + .
2 4 + 2 2 + 2 3 = 2 + (1)
,
3 = 1 + 2
4 = . 3 = 1 + 2 3
= 1 + 2 1 + 2
= 1 + + 2 2 (1 + )
We put these values in (1) and after simplifying
{2 1 + + 2 (2 2 )} 2
+ 2 2 1 + = 0
Equating Coefficients of E & 2 to be 0, we get
2 1 + + 2 2 2 = 0 (2)
2 2 1 + = 0 ..(3)
Adding (2) and (3), We get
2 2 1 + + 2 1 + + 2 = 0
2 2 + 2 + 2 + 2 = 0
2 + 2 + 2 + = 0
( + )2 + = 0
( + ) + 1 = 0
Either + = 0 or + = 1
| IJMER | ISSN: 22496645 |

www.ijmer.com

| Vol. 5 | Iss.3| Mar. 2015 | 9|

On ranges and null spaces of a special type of operator named . Part I


So for projection, the above two cases will be considered
Case (1): let + = 1 then = 1
Putting the value of b = 1 - a in equation (2) , we get
2 1 + + 2 2 1 + (1 )2 = 0
2 2 + 3 + 2 3 + 2 + 1 = 0
2 + 1 + 2 + 1 + + 2 + 1 = 0
[a( + 1)-1] [a( + 2) 1]=0
1

= +1

+2
+1

Then = +1 or

+2

Hence corresponding projections are


2
+1

+1

+2

( +1)
+2

Case (2) :- Let a + b = 0 or b =


So from Equation (2)
2 1 + + 2 22 2 = 0
2 2 + 3 + 2 = 0
+1 +2 1 =0
1

; (Assuming 0)

+1 +2

Therefore, =

1
+1 +2

Hence the corresponding projection is


2
+1 +2

So in all we get three projections. Call them A, B & C.


2

i.e. A= +2 +
2

and C =

1+

(1+)

+2

,B=

+1 +2

1+

3.2 Relation between A,B and C


A+B =
=
=
=
=

+2

(1+ )
+2

+1 +2

+1 +2

2 +1 +(+1)2 + 2
+1 +2
2 +2 +( +2)
+1 +2
2 +
+1
2
+1

+1

Hence ( + )2 = 2 2 + 2 + 2 = 2
+ + 2 =
2 = 0( + = )
= 0
Let = + 1
Then A =

2
+1

+1
2

, =

2
+1

and =

( 1)

Also = +1 + +1 +1 + +1
=

+
+1

+1
+1

Thus = .

| IJMER | ISSN: 22496645 |

www.ijmer.com

| Vol. 5 | Iss.3| Mar. 2015 | 10|

On ranges and null spaces of a special type of operator named . Part I


3.3 On ranges and null spaces of
We show that
= =
Where stands for range of operator E and for Null Space of E and similar notations for other operators.
Let = .
Therefore,
= =
=
=
=

1 + 2

1 2 + 3

1 2 + ( 1) 2

(Since 3 = 1 + 2 )

= =

Thus =
Therefore
Again if = =
=

2 + 1

(+ )
+1

Hence
Therefore =
Now , z = 0

2 + 1

=0

= 0
z
Therefore ,
2 + 1

Also z = 0

2 + 1

=0

=0

3 + 1 2

=0

= 0 = 0

Thus ,
Therefore , =
Now we show that
= : = = {: = }
Since A is a Projection ,
= : =
Let . Then = =
3 + 2

=
=
=

2 +

+1

3 + 1 2 + 2
+1
+ 2
+1

+1

= =
Thus {: = }
Conversely , Let = 2 =
So =

2 +
+1

+
+1

| IJMER | ISSN: 22496645 |

www.ijmer.com

| Vol. 5 | Iss.3| Mar. 2015 | 11|

On ranges and null spaces of a special type of operator named . Part I


Hence : =
Therefore, = {: = }
Next we show that
= {: = }
Since B is a Projection,
= : =
Let = 2 = 2
Hence (

2
( +1)

2 +

)z=

( +1)

( +1)

( +1)

i.e. = ( = ( +1) )

, : =
Conversely , let . =
Hence = =

2
3 2

( +1)

(+1)

But 3 2 = 1 2 2
= 2 = ( 2 )
So =

( +1)

2
( +1)

= =
{: = }
Therefore = {: = }
Now we show that = {}
Let
Then
If =
If =
Thus = =
+ = 0 + 1 = 0 = 0 ( + 1 0)
Therefore , = {0}
Theorem (1): If
= = +
such that
+ = and + =
Proof :- Since 1 2 = 2 1 = 0 ,
(1 + 2 )2 = 12 + 22 and (1 + 2 )3 =13 + 23
(1 + 2 )3 + (1 + 2 )2 = 13 + 23 + (12 + 22 )
= 13 + 12 + 23 + 22
= 1 + 1 + 1 + 2
= 1 + (1 + 2 )
Hence 1 + 2
Let 1 , 1 , 1 respectively projections in case of 1 ; 2 , 2 , 2 in case of
2 , , 1 + 2
1 + 2 =

12

( 1)1

12

22

22

| IJMER | ISSN: 22496645 |

( 1)2

1 + 2

www.ijmer.com

| Vol. 5 | Iss.3| Mar. 2015 | 12|

On ranges and null spaces of a special type of operator named . Part I


Thus 1 +2 = = 1 +2
Now we show that 1 +2 = 1 + 2
Let 1 +2 = 1 + 2 1 1
= 1 1 + 2 1 1 + 2
1 +2 1 + 2
Conversely, 1 + 2 = 1 + 2 ; where 1 1 , 2 2
Hence 1 1 = 1 2 2 = 2
But 2 1 = 2 1 1 = 0 ( 1 2 = 2 1 = 0)
Similarly 1 2 = 1 2 2 = 0
Hence = 1 + 2 = 1 1 + 2 2 + 1 2 + 2 1
= 1 + 2 1 + 2 = 1 + 2
Thus 1 +2
Therefore, 1 + 1 1 +2
Hence 1 +2 = 1 + 2
If 1 2 1 2
If 1 1 = if 2 2 =
Now 1 = = 2 = 2 1 = 2 1 = 0
=0
Therefore 1 2 = {0}
Hence 1 +2 = 1 2
So finally , We have
1 +2 = = 1 +2 = 1 2 = 1 2
Now we prove
+ =
Or + =
Let 1 2 1 = 0 = 2
(1 + 2 )z = 0
1 +2
Therefore 1 2 1+2
Conversely , let 1 +2 1 + 2 = 0
1 + 2 = 0
1 = 2
Hence 1 = 12 = 1 1 = 1 2 = 1 2 = 0
2
Also 2 = 22 = 2 2 = 2 1 = 2 1 = 0
2
So 1 2
Therefore , 1 +2 1 2
Hence 1 +2 = 1 2
Or , 1 +2 = 1 2
Theorem (2): If 1 2 ,then
1 2 = 2 1 1 2 = 2 1 2 1
Proof : Let 2 = 2 1 2 1
Let 2 2 . 2 = 1 + 2 ;
where 1 2 1 , 2 2 1
| IJMER | ISSN: 22496645 |

www.ijmer.com

| Vol. 5 | Iss.3| Mar. 2015 | 13|

On ranges and null spaces of a special type of operator named . Part I


Now, 1 2 1 1 2 1 1
2 1 = 1 1 1 = 1
2 1 = 1 1 1 = 1 (Since = )
Therefore , 1 = 1 1 = 1 2 1 = 1 2 1
2 2 1 2 2 2 1
2 2 2 2 = 2 , 2 1 1 2 = 0 (since = )
So 1 2 = 1 1 + 2 = 1 1 + 1 2 = 1 + 0 = 1
Also 2 1 2 = 2 1 = 1
Therefore , 1 2 = 2 1 2
Hence 1 2 = 2 1 2
Conversly , let 1 2 = 2 1 2 , 1 22 = 2 1 22
Hence 2 1 2 = 2 1
=
=

= 1

1 2 +22

2 1 2 + 2 1 22
1 2 +
1

1 22

(Since1 2 = 2 1 2 )

2 + 22 = 1 2

Let z 2 , 2 = . = 1 1
Also = 1 = 1 2 = 2 1 2 2
So y 2 1
Also , 2 = 2 1 = 2 ( 1 2 )
= 2 2 1 2 = 2 1 2 = 1 =
Hence 2
Also 1 = 1 1 = 1 12 = 1 1 = 0
1
Hence 2 1 . So z = + 2 1 + 2 1
2 2 1 + 2 1
Obviously , 2 1 + 2 1 2
Hence 2 = 2 1 + 2 1
Also, 2 1 2 1 = 2 1 1 = 2 0 = {0}
Hence 2 = 2 1 2 1
Theorem (3) : If 1 , 2 are two ,
2 1 = 2 1 2 2 = 2 1 2 1
Proof: Let 2 = 2 1 2 1
Let , 2 2 = 2 2 2 = 2 2 = 0
Hence 2 2
Let 2 = 1 + 2 ; 1 2 1 2 2 1
Hence 1 2 = 0, 2 1 = 0, 2 2 = 0, 1 1 = 1
Now 2 1 2 = 2 1 1 + 2 = 2 (1 1 + 1 2 )
= 2 1 + 1 2 = 2 1 + 2 1 2 = 2 1 2 = 2
=

2 1 2 2

12 + 1 1

2 1 2 = 0

Hence for any z, 2 1 2 = 0


Therefore ,2 1 2 = 0 2 1 = 2 1 2
Conversely , let the above relation hold

| IJMER | ISSN: 22496645 |

www.ijmer.com

| Vol. 5 | Iss.3| Mar. 2015 | 14|

On ranges and null spaces of a special type of operator named . Part I


Let 2 2 = 0 2 =

22 + 1 2

=0

1 1 = 1 1 1 = 0 , 1 1
, 2 1 = 2 2 1 = 2 2 1 2
= 0 2 1 2 = 0( 2 = 0 2 = 0)
, 1 2 1 1 2
Also 2 1 = 2 1 2 = 2 1 2 = 0
Hence 1 2 . Also 1 1
Hence 1 2 1
= 1 + 1 2 1 + 2 1
, 2 2 1 + 2 1
But 2 1 + 2 1 2
2 = 2 1 + 2 1
Also , 2 1 2 1 = 2 1 1 = 2 0 = {0}
2 = 2 1 2 1

REFERENCES
[1].
[2].
[3].

Chandra , P: Investigation into the theory of operators and linear spaces. (Ph.D. Thesis, Patna University , 1977)
Dunford, N. and Schwartz, J.: Linear operators Part I, Interscience Publishers, Inc., New York,1967, P. 37
Rudin, W. : Functional Analysis, Mc. Grow- Hill Book Company , Inc., New York, 1973,P.126

| IJMER | ISSN: 22496645 |

www.ijmer.com

| Vol. 5 | Iss.3| Mar. 2015 | 15|

Вам также может понравиться